Fibrinogen and lipid concentrations as risk factors for transient ischaemic attacks and minor ischaemic strokes. Issue 6803 (14th September 1991) - Qizilbash, N; Jones, L; Warlow, C; Mann, J
Abstract : OBJECTIVES–To determine whether fibrinogen and lipid concentrations are risk factors for ischaemic stroke. DESIGN–Case-control study with a population based comparison within the overall study. SETTING–Oxfordshire community stroke project and a neurology clinic. SUBJECTS–105 patients who had a transient ischaemic attack or minor ischaemic stroke and 352 randomly chosen controls matched for age and sex from the same general practitioners as the incident cases. 52 controls were ineligible or refused interview. 104 cases and 241 controls gave blood samples for analysis. MAIN OUTCOME MEASURES–Response to structured questionnaire, height, weight, blood pressure, and serum concentrations of fibrinogen and lipids. RESULTS–Adjusted for other variables, odds ratios of ischaemic stroke were 1.78 (95% confidence interval 0.91 to 3.48; p = 0.09) [corrected] for fibrinogen concentrations greater than 3.6 g/l; 1.73 (0.90 to 3.29; p = 0.09) [corrected] for total cholesterol concentrations greater than 6.0 mmol/l; 1.34 (0.69 to 2.61; p greater than 0.4) for low density lipoprotein cholesterol concentrations greater than 3.5 mmol/l; and 0.32 (0.15 to 0.69; p = 0.002) for high density lipoprotein cholesterol concentration greater than 1.2 mmol/l. Similar results emerged comparing only community derived cases with transient ischaemic attacks and controls. The effects of fibrinogen, total cholesterol, and high density lipoprotein cholesterol were significant in a test of trend after adjusting for all other variables in the study (chi 2 = 4.14, p less than 0.05; chi 2 = 4.31, p less than 0.05, and chi 2 = 12.15, p greater than 0.001, respectively). History of ischaemic heart disease and hypertension were the only other variables that showed significance, though both lost significance after adjustment (2.06, p = 0.08 and 1.53, p = 0.2, respectively). CONCLUSIONS–Fibrinogen and lipids are important risk factors for ischaemic stroke. The pattern of changes mirrors that found in ischaemic heart disease.